An aggregation-induced emission star polymer with pH and metal ion responsive fluorescence. Issue 42 (12th October 2016) - Zhao, Yuming; Zhu, Wen; Wu, Ying; Qu, Lin; Liu, Zhengping; Zhang, Ke
Abstract : A one-pot strategy from ring-opening metathesis polymerization was employed to prepare AIE-active star polymers, which were designed to have multi-responsive fluorescence to varied stimuli including pH, CO2, and metal ions. Abstract : A one-pot strategy was applied to synthesize an aggregation-induced emission (AIE) star polymer with pH and metal ion responsive fluorescence. Thestar polymer 1 was prepared via ring-opening metathesis polymerization (ROMP) of norbornene-based monomersM1, M2, M3, and crosslinkerbi-Nor . In this approach, M1 with a poly(ethylene glycol) side chain was polymerized to form poly(M1 ) as the hydrophilic arm of the star polymer. The mixture ofM2 (with phosphonate groups), M3 (with AIE fluorogen), andbi-Nor was then added in situ to extend poly(M1 ) chains and form the star polymer core. Subsequently, the functionalstar polymer 2 with phosphonic acid groups was derived by hydrolyzing the phosphonate groups in the core ofstar polymer 1, which demonstrated strong fluorescence when pH < 4 and weak fluorescence when pH > 5 in water. In addition, by virtue of the coordination of phosphonic acid groups with various metal ions, the aqueous solution ofstar polymer 2 (pH = 7 and 11) emitted significantly enhanced fluorescence in the presence of Mg 2+, Ca 2+, Cd 2+, Ni 2+, In 3+, Zn 2+, etc . The fluorescence intensity of the aqueous solution linearly increased with increasing concentration of metal ions in a wide range.